Nitrogen‐Doped Carbon as a Highly Active Metal‐Free Catalyst for the Selective Oxidative Dehydrogenation of N‐Heterocycles. Issue 15 (13th June 2022) - Li, Xun; Yuan, Ziliang; Liu, Yi; Yang, Hanmin; Nie, Jiabao; Wang, Guanghui; Liu, Bing
Abstract: N‐heteroarenes represents one of the most important chemicals in pharmaceuticals and other bio‐active molecules, which can be easily accessed from the oxidation of N‐heterocycles over metal catalysts. Herein, the metal‐free oxidative dehydrogenation of N‐heterocycles into N‐heteroarenes was developed using molecular oxygen as the terminal oxidant. The nitrogen‐doped carbon materials were facilely prepared via the simple pyrolysis process using biomass (carboxymethyl cellulose sodium) and dicyandiamide as the carbon and nitrogen source, respectively, and they were discovered to be robust for the oxidative dehydrogenation of N‐heterocycles into N‐heteroarenes under mild conditions (80 °C under 1 bar O2 ) with water as the green solvent. Diverse N‐heterocycles including 1, 2, 3, 4‐tetrahydroisoquinolines, indolines and 1, 2, 3, 4‐tetrahydroquinoxalines were smoothly converted into N‐heteroarenes with high to excellent yields (76–>99 %). Superoxide radical (⋅O2 − ) and hydroxyl radical (⋅OH) were probed as the reactive oxygen species for the oxidation of N‐heterocycles into N‐heteroarenes. More importantly, the nitrogen‐doped carbon catalyst can be reused with a high stability. The method provides an environmentally friendly and economical route to access important N‐hetero‐aromatic commodities. Abstract : Simpler and greener : Nitrogen‐doped carbon catalyst (NCC‐800) was readily prepared by the renewable biomass via the simple pyrolysis method, and it was found robust for catalyzing the oxidative dehydrogenation of N‐heterocycles at 80 °C under 1 bar O2 with water as the green solvent. Superoxide radical (˙O2 − ) and hydroxyl radical (˙OH) were probed as the reactive oxygen species for this transformation.